FRI0396 The veterans administration crystal registry from united states. (23rd January 2014) - Khanna, P.; Reimold, A.; Kerr, G.; Richards, J.S.; Chang, E.; Schumacher, H.R.; Khanna, D.
Abstract : Background: Gout is the most common inflammatory arthritis managed by healthcare providers of the Veterans Administration (VA) Healthcare System in the US. It affects ∼3.9% of the US population and is on a rise, especially in the elderly due to increased comorbidities. The CRYSTAL registry was created in 2008 as part of the initiative to standardize and improve care of gout patients at the VA. Objectives: Describe baseline characteristics of patients with gout from a prospective, longitudinal national registry. Methods: Gout patients who met the American College of Rhematology (ACR)/New York criteria from 5 VA sites in the US, are currently enrolled in this registry, and followed for response to therapy and development of complications as routine care in rheumatology clinics. At each visit, gout medications (past and current) and comorbidities are reviewed. Subjects answer standardized gout-related questions on flares, interval hospitalizations, HAQ-DI, pain and severity of disease, patient global assessment, and health behaviors. Joint exam is performed to document disease activity. Laboratory parameters including acute phase reactants, serum urate, creatinine, and complete blood counts are monitored. All sites are approved by the Institutional Review Board for consent of blood draw for serologic profiling and genetic testing at the first visit. In this analysis, data is presented as means± standard deviations or percentages. Results: To date, 258 patients are enrolled, and 163 have complete data. Of these, 99% are male, aged 66.8 (10.1) years. Caucasian and African American races were well represented, (n=73, 43% and n=85, 50% respectively). Mean age of gout symptom onset was 51.1 (15.3) years, mean age of gout diagnosis 54.1 (14.5) years, and disease duration was 15.2 (13) years. Three fourths of patients showed evidence of urate crystals on polarized microscopy (n=62/82). Mean serum urate was 7.5 mg/dl (2.3, n=97) and 56.7% of patients had a serum urate >7.0 mg/dl (n=55/97). HAQ-DI was 0.9 (0.8, n=78), severity of gout was rated as 6.7 (3.2) on a scale of 0-10 (n=77), and majority of flares were monoarticular (87.4%). Eighty one (46%) patients reported experiencing 4 flares in the past 12 months and 34 (42%) had tophi on physical exam. Comorbidities were common and included hypertension (n=60, 36.8%), hyperlipidemia (n=31, 19%), diabetes and obesity (n=24, 14.7% each). More than 90% (n=90) had renal impairment [CKD stage 2-4, average GFR=54 ml/min (16.8)]. Allopurinol was the most commonly used urate-lowering agent (ULT) (n=98, 60.1%), febuxostat (n=12, 7.4%) and probenecid was prescribed in only one patient. For acute treatment of gout, colchicine use was reported in 58.5% (n=95), prednisone 11.7% (n=19), and NSAIDS 9.8% (n=16). Conclusions: This registry highlights important aspects of gout such as high frequency of gout flares, the extent of renal impairment, and the growing need to initiate ULT in a large proportion of these patients. Hence, CRYSTAL is a critical repository of medical observations that will prospectively inform on quality of care, adherence to medications, genetic profiles, and result in better understanding of treatment response. Disclosure of Interest: None Declared